The Reprimo gene family member, reprimo-like (rprml), is required for blood development in embryonic zebrafish - Stanic, Karen (Sci Rep, 2019)
The Reprimo gene family comprises a group of single-exon genes for which their physiological function remains poorly understood. Heretofore, mammalian Reprimo (RPRM) has been described as a putative p53-dependent tumor suppressor gene that functions at the G2/M cell cycle checkpoint. Another family member, Reprimo-like (RPRML), has not yet an established role in physiology or pathology. Importantly, RPRML expression pattern is conserved between zebrafish and human species. Here, using CRISPR-Cas9 and antisense morpholino oligonucleotides, we disrupt the expression of rprml in zebrafish and demonstrate that its loss leads to impaired definitive hematopoiesis. The formation of hemangioblasts and the primitive wave of hematopoiesis occur normally in absence of rprml. Later in development there is a significant reduction in erythroid-myeloid precursors (EMP) at the posterior blood island (PBI) and a significant decline of definitive hematopoietic stem/progenitor cells (HSPCs). Furthermore, loss of rprml also increases the activity of caspase-3 in endothelial cells within the caudal hematopoietic tissue (CHT), the first perivascular niche where HSPCs reside during zebrafish embryonic development. Herein, we report an essential role for rprml during hematovascular development in zebrafish embryos, specifically during the definitive waves of hematopoiesis, indicating for the first time a physiological role for the rprml gene.